Penerapan Good Governance Dalam Meningkatkan Kinerja Organisasi Pemerintahan Di Kantor Desa Lamatti Riattang Kecamatan Bulupoddo - Insan, Khaerul; Juniati, Sri rahayu; Hasyim, Syamsiah; Nursyafika (Jurnal Ilmiah Administrasita', 2025)
This study aimed to determine the implementation of good governance to improve the performance of government organizations in the Lamatti Riattang Village Office, Bulupoddo District. The research method used was qualitative descriptive research - data collection through observation, interviews and documentation. Data analysis techniques were data collection, reduction, presentation, and conclusion. The results indicated that the implementation of good governance in improving the performance of government organizations was good. Responsibility had been running well. Implementing government transparency in managing a village government budget refers to existing regulations. All village officials were given their respective authorities and they carried them out with the SOP. There was no suggestion box, so the public could directly contact the WhatsApp number for complaint service if there was a complaint. The effectiveness was seen from the existence of a document stating the accountability of the village head in evaluating activities. All program implementations were carried out well because of community support. Every activity always involves the community. If the village government carried out a development, the community was enthusiastic to help. The success of the development of the village government program had been going well. This can be seen in the maintenance of concrete rebars. Administrative guidance for dasawisma carried out by PKK Lamatti Riattang. Procurement of arts and sports festivals at the hamlet level to commemorate the Republic of Indonesia's Independence Day. Development of waste bank management aimed to educate the community about the economic value of waste and make Lamatti Riattang village a waste-free village. This research can guide the Village Government in improving the performance of government organizations at the Lamatti Riattang Village Office, Bulupoddo District.